EFEKTIFITAS PELAKSANAAN PROGRAM ASISTENSI MENGAJAR TERHADAP MUTU PEMBELAJARAN DI SMA NEGERI 2 MATARAM - Liza Hanim; Muh. Zubair; Bagdawansyah Alqadri; Muhammad Mustari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Currently, education in Indonesia is in the stage of improving the quality of learning. Improving the quality of learning is very important to achieve student competencies as expected, so that schools can produce quality graduates. Improving the quality of learning can be done through collaboration between universities and schools. SMA Negeri 2 Mataram is one of the leading high schools in the city of Mataram, SMA Negeri 2 Mataram has become one of the student placement schools in implementing the program. The purpose of this study was to determine the effectiveness of the implementation of the teaching assistance program on the quality of learning at SMA Negeri 2 Mataram and what factors influence it. This study uses a qualitative method, with a case study method. Data were collected through interview, documentation and survey methods.